Analysis of the Importance of Mastering English for Waiters at Several Restaurants in Ubud Bali - Wayan, Pastini Ni; Lilasari, Luh Nyoman Tri; Muliana, I Wayan; Ariasri, Nyoman Reni (Newinera Publisher, 2024)
This research aims to find out and examine the use of types of grammatical errors in the sentences used by waiters in serving consumers when serving food and drinks in several restaurants in Ubud, Gianyar. This research uses a qualitative research approach. The population of this research focuses on waiters in several restaurants in the Ubud Gianyar area, Bali. The results of the research show that the use of English grammar in using English sentences by waiters and waiters in communicating with guests at several restaurants in Ubud Gianyar can be concluded that their mastery of English is very weak in using words such as Miss. Mrs. Ms, Mrs. Sir, Sir, they have no understanding of those words. Of the four classifications, the most common errors are omission classification errors and replacement classification errors. Of the four classifications of addition errors, only 2 sentences were found, the classification of omission errors found 38 deletion errors (9 noun deletion errors, 16 to be errors, 6 article deletion errors, 3 pronoun deletion errors and 4-word deletion errors. auxiliary work). Meanwhile, the classification of substitution errors is less than that of omission errors, namely there are only 12 errors (2 subject-predicate substitution errors. 2 pronoun form errors, 7-word usage errors and 1 preposition substitution error.